2012
DOI: 10.1016/j.amjopharm.2011.11.003
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Dementia on Medication Use and Adherence Among Medicare Beneficiaries With Chronic Heart Failure

Abstract: Background Alzheimer disease and related disorders (ADRD) are prevalent in older adults, increase the costs of chronic heart failure (CHF) management, and may be associated with undertreatment of cardiovascular disease. Objective The purpose of our study was to determine the relationship between comorbid ADRD and CHF medication use and adherence among Medicare beneficiaries with CHF. Methods This 2-year (1/1/2006–12/31/2007) cross-sectional study used data from the Chronic Condition Data Warehouse of the C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
8
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 45 publications
3
8
0
Order By: Relevance
“…We found that the level of inflammation and amyloid metabolism is gender specific, which is in line with the results of multicenter studies which show that of the patients with CHF and systolic dysfunction, a large percentage has a diagnosis of Alzheimer’s disease and related disorders [21], and that women have a higher morbidity of dementia [20], [21].…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…We found that the level of inflammation and amyloid metabolism is gender specific, which is in line with the results of multicenter studies which show that of the patients with CHF and systolic dysfunction, a large percentage has a diagnosis of Alzheimer’s disease and related disorders [21], and that women have a higher morbidity of dementia [20], [21].…”
Section: Discussionsupporting
confidence: 89%
“…Whereas causal relationships between CHF and AD for human [21] have been described, animal studies are rare. Here we presented data indicating that CHF can increase a gender specific risk of developing cognitive dysfunction by modulation of amyloid processing and inflammation detected at the level of gene transcription and translation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The regression analysis performed revealed two other factors besides higher cognitive score associated with the use of ACEI/ARBs and β-blockers, namely lower age and higher ADL score. Similar results have been found in a study performed in the USA, where people with Alzheimer's disease and concomitant heart failure were less likely to receive evidence-based medications (ACEI/ARBs, selective β-blockers and MRAs) than people with heart failure without comorbid Alzheimer's disease [49]. Another study performed in Sweden found that people with cognitive impairment were treated to a lesser extent with ACEIs and β-blockers compared with people with MMSE > 23, indicating under-treatment of some cardiovascular diseases among the elderly with cognitive impairment.…”
Section: Discussionsupporting
confidence: 87%
“…Non-centrally active angiotensin-converting enzyme inhibitors are associated with a greater risk of dementia and functional disability [48]. Vasodilation, which increases the use of cerebral hypoperfusion are more commonly used in heart failure patients with dementia, than other heart failure drugs [49]. Surprisingly, the use of digoxin in heart failure improved cognition, presumably related to an increase in cardiac output [50].…”
Section: Associations With Heart Failure and Cognitive Declinementioning
confidence: 98%